Valutazione dei processi assistenziali e del carico economico dei soggetti con ospedalizzazione incidente di infarto acuto del miocardio mediante il Data Warehouse DENALI - Mantovani, Lorenzo G.; Fornari, Carla; Madotto, Fabiana; Riva, Michele A.; Merlino, Luca; Chiodini, Virginio; Cesana, Giancarlo (Farmeconomia. Health economics and therapeutic pathways, 2011)
Aims: this study wants to estimate the economic burden of incident Acute Myocardial Infarction (AMI) registered in Lombardy (about 9.2 million residents). Method and results: a longitudinal study was conducted using a Data Warehouse (DENALI) that organised Healthcare Administrative databases of Lombardy related to eligibility criteria, hospital discharges (HDs), pharmaceutical and outpatient claims of citizens. All individuals with a HD for a first event of AMI during 2003 were identified and followed for 12 months. During 2003 12,049 individuals (64% males, mean age 70 +/-13 y.o.) had a HD for incident AMI. The total cost during the first year was € 163 million, corresponding to the 1% of the healthca re budget of Lombardy. The monthly cost in the first year was € 1,249 per person (77% attributable to HDs, 15% to pharmaceuticals and 8% to outpatient care). While most of the uptake of drugs used in secondary prevention was quick and happened in the first 3 months after the index event, the phenomenon of non persistence at 12 months was relevant. Conclusion: this large study on the burden of AMI shows the epidemiologic, economic and clinical impact of the disease. DENALI, with its large population followed over time, is a powerful and dynamic tool for epidemiologic and health economic research.